Lifestyles of the nursing student of a private university in times of COVID-19, Chiclayo 2021 - Benavides Castillo, Mary Katherine (2022)
Objective: Describe and analyze the lifestyles of the Nursing student of a Private University in times of COVID-19, Chiclayo 2021. Method: The study methodology was qualitative with a descriptive approach, and the sample was saturated with 12 students from the VIII Nursing cycle enrolled in the 2021-I semester, which was determined by saturation and redundancy and the sampling was non-probabilistic for convenience. In data collection, a semi-structured interview guide was used, validated through the judgment of 3 experts and a pilot study. Data analysis was determined by content analysis. During the development of the research, the principles of scientific rigor and bioethics were considered. Main results: Three categories were obtained as results: a) Eating behaviors during the COVID-19 pandemic, b) Sleep disorders due to the effects of the COVID-19 pandemic, c) Sedentary lifestyle and physical activity during the COVID-19 pandemic. Overall conclusion: The results shown in this study indicate that, during the. COVID-19, the lifestyles of nursing students have been modified, where unhealthy lifestyles prevail.